How we used coordinated trials and meta-analysis to evaluate interventions to increase varietal turnover - Kramer, Berber; Trachtman, Carly; Wiecek, Witold (International Food Policy Research Institute, 2024)
This blog post details the use of coordinated trials and meta-analysis to evaluate interventions aimed at increasing varietal turnover in agriculture. The study focuses on the challenge of slow adoption and limited turnover of new crop varieties, which can hinder agricultural productivity and resilience. By coordinating trials across multiple regions and integrating data through meta-analysis, the research team was able to assess the effectiveness of various interventions designed to accelerate varietal adoption. The findings highlight the importance of context-specific strategies and the role of market incentives, extension services, and farmer engagement in promoting the uptake of improved varieties. The approach underscores the value of rigorous, collaborative research in guiding evidence-based policy decisions that can enhance agricultural innovation and food security.